Planning the market and the industrial relations system a critique to the regulation school in the era of globalization - Sanchez, Phoebe Zoe Maria U. (Danyag :the UPV journal of humanities and social sciences, 2005)
"This theoretical paper is a counter-critique to the critique of the Regulation Theorists to Structural Marxism's 'determining role of the economic in the last instance of capitalist reproduction'. The Regulation Theory is popularized by the French School known as planification (market regulation) where the State intervenes through economic policies intended to bridge the gap between capitalists and labour groups to reach compromise equilibrium for 'social cohesion' and for a better operation fo the industrial complex and the market system. These state regulations known as 'modes of regulation' are usually in the form of welfare policies i.3., worker's union benefits, workers' insurance system, public health care, public education, asset redistribution such as public housing and land for the landless programs, etc. discovered by French Scholars to be crucial to capitalists reproduction. Thus, positing that it is the state intervention or the political that has the final determining role in the last instance of capitalist reproduction and not the economic. The study also focuses on the changes of the relationship between capital and labor through state mediation known as 'regulation' from the period fo Fordism to the era of post-Fordism."